Gambaran Ketidakadilan terhadap Perempuan dalam Novel Al-Hub Fi Zamani Al-Nafthi Karya Nawal Sa’dawi (Sebuah Kajian Feminisme) - Julian, Hendri; Jannah, Raudhatul; Yusliza, Yusliza; Burlianda, Muhammad (Al-Fashahah: Journal of Arabic Education, Linguistics, and Literature, 2025)
This study aims to describe the problems seen from a feminist perspective, in the form of forms of injustice against women contained in the novel "Al Hubb fi Zamani Al Nafthi" by Nawal El Saadawi. Nawal El Sadawi, is a famous writer who is very sensitive in expressing the feelings of women who experience injustice. The method to uncover injustice against women is by descriptive analysis of the injustice events contained in the novel "Al Hubb Fi Zamani Al Nafthi" using a feminist and gender approach. The results of this study indicate that there are several problems, including: first, feminist literature is an approach that aims to describe gender issues that are dominated by men, which are characterized by gender inequality. Second, the gender issues contained in the novel are violence against women, women's subordination, stereotypes or negative labeling against women, and physical violence that occurs in the household.